Mini Encyclopedia: Artificial Intelegence Development For Accountants’ Necessity - Femba Akris Diantoro; Nanang Asfufi (ARTOKULO : Journal of Accounting, Economic and Management, 2024)
The direction of Artificial Intelegence development which is quite rapid can have a positive value in helping accountants be more effective and efficient in carrying out their duties, by adding a soft skill can support existing competencies in human resources as a communication tool developed by many companies throughout the world.  Distribute relevant information to users through intelligent technology. This situation can be explained through the Society 5.0 concept which enables machines based on Industry 5.0 Technology. Helping the community overcome various problems in a sustainable manner. This research uses descriptive qualitative secondary data which looks at phenomena so that they can explain the research. The results of this research evaluate the prospects of artificial intelligence to make the work of accountants easier, which can include large amounts of data that can be accessed easily and safely in future applications in the digital era 5.0, clearly the results of researchers who carry out research in the past and development every year, so that updates this can be the starting point for turning weakness into extraordinary progress